Monoadventitial multiple pulmonary hydatidosis - Ferreira Buadas, Nelson; Ferreira, Clivio (Cirugía del Uruguay, 1975)
The case of a patient with multiple monoadventitial pulmonary hydatidosis is described. In a large adventitial sac of the upper right Jobe, there were 5 hydatids of different sizes, ranging between 2 and 7 cm in diameter. The possible pathogenic mechanisms of this case are analyzed. It is determined that it could be a case of endogenous vesiculiz¡tion, with unapparent elimination of the main membrane or, an exceptional case of exogenous vesiculization.